2013
DOI: 10.1371/journal.pone.0061802
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic-Induced Hepatocyte Proliferation Associated with Constitutive Active/Androstane Receptor (CAR) or Peroxisome Proliferator-Activated Receptor α (PPARα) Is Enhanced by Pregnane X Receptor (PXR) Activation in Mice

Abstract: Xenobiotic-responsive nuclear receptors pregnane X receptor (PXR), constitutive active/androstane receptor (CAR) and peroxisome proliferator-activated receptor α (PPARα) play pivotal roles in the metabolic functions of the liver such as xenobiotics detoxification and energy metabolism. While CAR or PPARα activation induces hepatocyte proliferation and hepatocarcinogenesis in rodent models, it remains unclear whether PXR activation also shows such effects. In the present study, we have investigated the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…In these respects, PXR appears to function in the maintenance of the immature phenotype, rather than a promoter of stem cell differentiation, as is the case for CAR. This finding appears consistent with several previous reports demonstrating that PXR suppresses the proliferation of cancer cells by upregulating cyclin-dependent kinase (CDK) inhibitor p21, that ectopic PXR expression in neuroblastoma cells results in growth suppression (Misawa et al, 2005), and that PXR activation alone has no effect on cell proliferation in mouse liver (Shizu et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…In these respects, PXR appears to function in the maintenance of the immature phenotype, rather than a promoter of stem cell differentiation, as is the case for CAR. This finding appears consistent with several previous reports demonstrating that PXR suppresses the proliferation of cancer cells by upregulating cyclin-dependent kinase (CDK) inhibitor p21, that ectopic PXR expression in neuroblastoma cells results in growth suppression (Misawa et al, 2005), and that PXR activation alone has no effect on cell proliferation in mouse liver (Shizu et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Recently, we have demonstrated that PXR activation accelerates CAR-dependent as well as growth factor-mediated proliferation of murine hepatocytes by increasing the sensitivity to proliferation stimuli through the downregulation of cyclin-dependent kinase inhibitor proteins (Shizu et al, 2013(Shizu et al, , 2016. We thus co-treated mice with TCPOBOP and imazalil to verify whether imazalil treatment could accelerate hepatocyte proliferation induced by TCPOBOP through mPXR activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this well-known function, recent studies have expanded the roles of PXR, which include the regulation of glucose or lipid metabolisms in the liver (Sui et al, 2011;Chang and Waxman, 2006;Hukkanen, 2012;Gotoh and Negishi, 2015;Spruiell et al, 2014). In addition, we have recently demonstrated that PXR activation enhances hepatocyte proliferation mediated by CAR or peroxisome proliferator-activated receptor α (PPARα) activation: Although treatment of mice with pregnenolone 16α-carbonitrile (PCN), a PXR agonist, alone did not induce hepatocyte proliferation, co-treatment of mice with PCN and CAR or PPARα agonist showed intense hepatocyte proliferation compared to single treatment with CAR or PPARα agonist (Shizu et al, 2013), which probably results from the PXR-mediated down-regulation of cell cycle suppressor genes (Shizu et al, 2016). Because CAR-and PPARα-dependent hepatocyte proliferation is associated with liver cancer in rodents, the exposure to PXR activators might increase the risk of liver cancer, that is, PXR-activating capability of chemicals can be a potential risk of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, PXR activation also induces differentiation of osteoblasts and apoptosis of osteoclasts and certain leukemia cells (Austin et al, 2015; Hassen et al, 2014; Igarashi et al, 2007; Kameda et al, 1996; Tabb et al, 2003), suggesting that control of cell proliferation by PXR is likely tissue and cell-specific. A similar theme plays out in cancer cells, in which, PXR differentially regulates cell growth through multiple mechanisms in a variety of cancers, including liver, prostate, breast, ovarian, endometrial, cervical, and colon (Braeuning et al, 2014; Kakehashi et al, 2013; Koutsounas et al, 2013; Luisier et al, 2014; Ma et al, 2015; Niu et al, 2014; Pondugula and Mani, 2013; Qiao et al, 2013; Ross et al, 2010; Rouquie et al, 2014; Shizu et al, 2013; Tinwell et al, 2014). Additionally, PXR is involved in regulating metastasis of cancer cells (Gupta et al, 2008; Masuyama et al, 2007; Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 85%